2019
DOI: 10.1111/jfpp.14127
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and reliable method for the specific detection of aflatoxigenic fungi in groundnut and rice samples

Abstract: Aflatoxin contamination is a serious food safety and economic concern for the agriculture and processing industry throughout the world. Aflatoxins are the most potent carcinogens; therefore, an early detection of aflatoxin‐producing fungi is essential for ensuring food safety. In the present work, a rapid and sensitive PCR method for the detection of potential aflatoxin‐producing molds in groundnut and rice samples was developed. This PCR assay can detect the aflatoxigenic fungi in the contaminated samples dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Pulverized mycelia were added to 1300 microliters of lysis buffer (100 mM Tris HCL [pH 8.0], 50 mM EDTA, 3% SDS), which were then incubated at 65 o C for 30 minutes. The technique outlined by Bansal et al 2019 was used to extract the fungal genomic DNA. In 30 microliters of TE buffer, the isolated DNA pellet was dissolved.…”
Section: Fungal Dna Isolation Extractionmentioning
confidence: 99%
“…Pulverized mycelia were added to 1300 microliters of lysis buffer (100 mM Tris HCL [pH 8.0], 50 mM EDTA, 3% SDS), which were then incubated at 65 o C for 30 minutes. The technique outlined by Bansal et al 2019 was used to extract the fungal genomic DNA. In 30 microliters of TE buffer, the isolated DNA pellet was dissolved.…”
Section: Fungal Dna Isolation Extractionmentioning
confidence: 99%
“…Studies have reported the development of PCR assays (and derived techniques) for the identification and/or detection of A. flavus and/or A. parasiticus (Chen et al, 2002;Sugita et al, 2004;González-Salgado et al, 2008;Sardiñas et al, 2010;Luo et al, 2012;Wang et al, 2012;Ahmad et al, 2014;Bansal et al, 2019). However, many studies have been based on a restricted number of sequences for primer design and/or a small number of strains for assay development.…”
Section: Primersmentioning
confidence: 99%